Time is health: management of Parkinson’s disease in primary care: a retrospective quantitative study of diagnostic and therapeutic timelines - Sabine Bayen; Xavier Lagon; Charles Cauet; Marc Bayen; Teddy Richebe; Nassir Messaadi; Matthieu Calafiore (BMC Primary Care)
Abstract Background Parkinson’s disease is a neurodegenerative disorder which can be difficult to diagnose due to the non-specificity of the initial symptoms. The objective of our study was to objectify and quantify the delay of the diagnostic process and to identify the factors that influence it. Methods An exploratory quantitative, cross-sectional, retrospective, observational study was conducted from 22 March 2023 to 31 March 2024 among general practitioners (GPs) practising in France who were asked to study their patient files concerning the care pathways of their patients with Parkinson’s disease. The data was collected using a standardised, anonymised online questionnaire (Limesurvey®), the link to which was distributed via email. The questionnaire provided detailed information on the key dates of diagnosis and follow-up, and on the symptoms reported by patients and documented by doctors. Results The diagnostic pathway for Parkinson’s disease is substantiated by the observation of protracted delays. On average, patients take more than three years to obtain a formal diagnosis and to receive appropriate treatment. The delays experienced are primarily attributable to prodromal non-visible non-motor symptoms, for which referral delays are tripled in comparison to visible motor symptoms. Challenges in accessing a neurologist and the frequent necessity for unnecessary complementary exams also contribute to the delays. Conclusion Our results underscore the pivotal role of GPs in the early detection of Parkinson’s disease, particularly in its prodromal stage marked by non-visible non-motor symptoms. While the diagnostic hypothesis was confirmed in most cases (70%) by neurologists, specific training of GPs in Parkinson’s disease with recognition of non-motor symptoms and treatment initiation would accelerate the process of diagnosis and referral to a neurologist and potentially reduce diagnostic and therapeutic times.